STUDI KUALITAS PERAIRAN PANTAI DI KAWASAN INDUSTRI PERIKANAN, DESA PENGAMBENGAN, KECAMATAN NEGARA, KABUPATEN JEMBRANA - Poppo, Ary; Mahendra, M S; Sundra, I Ketut (ECOTROPHIC : Jurnal Ilmu Lingkungan (Journal of Environmental Science), 2012)
Bali Strait represent the strait dissociating Bali Island with Java Island. As an area of fishing zone, Bali Straitowns a significant fishery potency, especially lemuru fish (Sardenella lemuru). For the facility of fisherman haul,governmental developed the Center of Fish Landing which is located at Pengambengan village of Negara Subdistrict.Within the area also exists the fishery industries which is operated for fish canning and fish meal.The aim of this research was to determine the properties of pollutant from waste water that was produced byfishery industry, as well as to know the quality of coastal waters destined for the aquatic life that produced by industrialactivity.The sample of sea waters was taken from 11 locations and one sample was taken from waste water effluent one ofone factory at Pengambengan village. The result of analysis was used to calculate the pollution index and comparationwas made to the Governor Regulation Number 8 year 2007.The finding of the study shows that the pollutant properties of the waste water produced by fishery industry haveexceeded the maximum level of quality standar covering parameters of TSS, TDS, BOD5, COD, sulfide hydrogen (H2S),degree of acidity (pH), and ammonia (NH3). Calculation result of respective sampling location, shows that the value ofthe pollution index varied from slight, medium, and heavy pollution levels.
Keywords: TSS, BOD5, COD, pollution index.